PENGARUH PENGGUNAAN EKSTRAK DAUN NIMBA (Azadirachta indica A. Juss) TERHADAP PENGENDALIAN KUMBANG (Tribolium castaneum) - Armi Desiputra Permana; Rahmat Wiradimadja; Iman Hernaman (JURNAL ISTEK, 2012)
The study was aimed to know the effect and best usage level of neem leaf extract on rice bran to life number of Tribolium castaneum and weight loss of rice bran. The research used an experimental method. The study used Completely Randomized Design with four treatment neem leaf extract that R0 = 0%, R1 = 2%, R2 = 4% and R3 = 6%, each is repeated five replications. The result showed that neem leaf extract usage up to level 6% on rice bran providesa realimpactto life number of Tribolium castaneum and weight loss of rice bran, and used neem leaf extract on level 6% to givelife numberof Tribolium castaneum and the lowest weight loss.